Cognition and Frailty in Patients With Heart Failure: A Systematic Review of the Association Between Frailty and Cognitive Impairment - Faulkner, Kenneth M.; Uchmanowicz, Izabella; Lisiak, Magdalena; Cichoń, Ewelina; Cyrkot, Tomasz; Szczepanowski, Remigiusz (Frontiers in Psychiatry, 2021)
Background/Aim: Pathological processes associated with aging increase the risk of cognitive deficits. Frailty syndrome may significantly accelerate these pathological processes in elderly patients with heart failure. The objective of this review was to better understand the association between frailty syndrome and co-occurring cognitive decline in patients with heart failure. Methods: We conducted a systematic review based on PubMed/MEDLINE, Scopus, EMBASE, and CINAHL as databases. The search followed the method described by Webb and Roe. For inclusions, the studies were selected employing cross-sectional and longitudinal designs. The included studies had to evaluate frailty syndrome and cognitive impairments among participants with heart failure. As we were interested in older adults, the search was limited to individuals >65 years of age. The search was limited to primary research articles written in English published since the year 2000. Results: Of the 1,245 studies retrieved by the systematic review, 8 relevant studies were enclosed for the full-text review. Our review revealed that most studies of patients with HF demonstrated evidence of an association between greater frailty and cognitive impairment. In particular, six studies reported evidence for the significant association between higher levels of frailty and cognitive impairment in patients with heart failure. The remaining two studies failed to find an association between frailty and cognitive impairment. Conclusions: The development of frailty and cognitive impairment in heart failure is particularly important because this cardiovascular disease is a common cause of both morbidity and mortality in the world. The results of this review fill the existing gap in the literature related to the identification of clinical factors linked with frailty syndrome that contribute to cognitive impairment in patients with a diagnosis of heart failure. The prevalence of overlapping frailty and cognitive impairment in patients with heart failure, therefore, necessitates a routine assessment of these components in the care of patients with cardiovascular disease.